2001
DOI: 10.1007/s002130000630
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of MK-801-induced behaviour by noradrenergic agents in mice

Abstract: Rationale: Inhibition of glutamatergic Nmethyl-D-aspartate (NMDA) receptors following the administration of NMDA receptor antagonists results in psychotic-like behaviour. Whereas it is known that pharmacological manipulation of dopaminergic and serotonergic pathways affect this drug-induced psychosis, a role for noradrenaline has not yet been clearly defined. Objectives: Thus, in the present study, we assessed a possible role for noradrenaline in the behavioural response to the non-competitive NMDA receptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
(64 reference statements)
2
14
0
Order By: Relevance
“…It has also been proposed that rearing is mediated by noradrenergic pathways, in contrast to horizontal locomotion, which more reflects the action of the mesolimbic dopamine system (Miyamoto et al 1984;Masuo et al 1995). Consistent with this idea are experiments in CD-I mice showing that noradrenaline tends to antagonize MK-801 effects (Harkin et al 2001), which would predict the inhibitory effects we observed on rearing. Several other drugs have differential effects on horizontal versus vertical locomotion.…”
Section: Discussionsupporting
confidence: 54%
“…It has also been proposed that rearing is mediated by noradrenergic pathways, in contrast to horizontal locomotion, which more reflects the action of the mesolimbic dopamine system (Miyamoto et al 1984;Masuo et al 1995). Consistent with this idea are experiments in CD-I mice showing that noradrenaline tends to antagonize MK-801 effects (Harkin et al 2001), which would predict the inhibitory effects we observed on rearing. Several other drugs have differential effects on horizontal versus vertical locomotion.…”
Section: Discussionsupporting
confidence: 54%
“…Other studies have shown that systemic administration of prazosin can attenuate the locomotor response to cocaine, the NMDA receptor antagonist MK-801, and the DA reuptake inhibitor GBR 12783 (Arnt 1995;Dickinson et al 1988;Drouin et al 2002a;Harkin et al 2001;Mathe et al 1996;Snoddy and Tessel 1985;Svensson et al 1995;Wellman et al 2002). Thus, the experiments described herein tested the hypothesis that activation of α 1 -adrenoceptors in the prefrontal cortex and ventral tegmental area of the rat modulate the locomotor response to MDMA.…”
Section: Introductionmentioning
confidence: 79%
“…Although the clinical significance of a 1 -adrenoceptor blockade for the therapeutic properties of quetiapine and other antipsychotics remains unclear, a 1 -adrenoceptor antagonists are active in several models predictive of clinical activity (Brunello et al 1995). They improve functioning in models of cognitive deficits in schizophrenia Geyer 1997, 1999;Carasso et al 1998) and attenuate hyperactivity elicited by amphetamine, dizocilpine and phencyclidine (Harkin et al 2001;Drouin et al 2002).…”
Section: Discussionmentioning
confidence: 98%